(untitled) (Conference Zone, 2021)
The parameters of the reproductive biology of rainbow trout female (Oncorhynchus mykiss), grown from imported fertilized eggs in the conditions of the Tashkent region of Uzbekistan were studied. Females of the studied generation reached their first sexual maturity at the age of 3 when they reached a total body length of 40-66 (55.2) cm, a total body weight of 1370 - 5450 (2963.6) g. Mass of gonads at stage IV in fish sampled for incubation campaign was 300 - 900 (532.4) g. The absolute fecundity was 2520 - 15660 (5981.4) eggs. The sizes of individual eggs varied in the females of the herd 3.6 - 6.0 mm, the average indi-vidual sizes of mature eggs were on average 4.43 - 5 (4.86) mm in the herd